Maintenance therapy for AML after allogeneic HCT - Nayak, Rahul K.; Chen, Yi-Bin (Frontiers in Oncology, 2022)
Allogeneic hematopoietic cell transplant (allo-HCT) for eligible patients with acute myeloid leukemia (AML) in first complete remission is a central treatment paradigm to achieve durable remission. However, disease relapse after allo-HCT remains a significant concern and generally portends a poor prognosis. There is significant interest regarding the role for maintenance therapy after allo-HCT for patients with high risk of relapse, regardless of the presence of measurable residual disease. While there are currently no therapies approved for maintenance therapy for AML after allo-HCT, there is a number of ongoing investigations examining the role of maintenance therapies that include targeted agents against FLT3-ITD or IDH mutations, hypomethylating agents, immunomodulatory therapies and cellular therapies. In this review, we examine the current landscape and future strategies for maintenance therapy for AML after allo-HCT.